2015
DOI: 10.1007/s13369-015-1794-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response Changes of Seismic Isolated Building Due to Material Degradation of HDRB

Abstract: This study investigates the variations in the mechanical properties of high-damping rubber bearings HDRBs on the dynamic response of multi-story seismic baseisolated building subjected to bidirectional near-fault ground motions. Variations in the mechanical properties of HDRB due to temperature, aging and scragging recovery are considered. Nonlinear response analyses of a six-story base-isolated building subjected to seven pairs of bidirectional near-fault ground motions with pulse type were conducted using fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The laminated rubber bearing offers a benefit to practical applications owing to its standardized modes, whereas the technical challenge of the associated degradation still gets some existing works attention . FSBs have the advantage of being insensitive to seismic ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…The laminated rubber bearing offers a benefit to practical applications owing to its standardized modes, whereas the technical challenge of the associated degradation still gets some existing works attention . FSBs have the advantage of being insensitive to seismic ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about durability have been identified by several researchers in recent years (Pan et al 2005, Hamaguchi et al 2009, Van Engelen and Kelly 2015, Mazza 2019. Various researchers have also addressed the subject of changes to mechanical properties of BI impacting performance (Gheryani et al 2015), and tests have shown that base isolators do not perform as designed for 2 months after an earthquake owing to cyclic straining history on the rubber, and draws attention to the implications for pre-earthquake and aftershock events (Siringoringo and Fujino 2015). There is generally a lack of rigorous and independent research around the subject of base isolator durability, inspection, and replacement.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Finally, the response of the FSBs shifts between the sticking and sliding phases, at the breakaway and motion reversals, highlighting a static friction coefficient greater than the dynamic one. 23 A few studies on the effects of ageing on isolation systems 24-26 after 20, 30, and 40 years of use have been carried out, as well as recent numerical investigations [27][28][29] introducing modification factors accounting for ageing and air temperature effects. The aim of the present work is to investigate the effects of variability of the mechanical properties of elastomeric and sliding bearings, both during the design life and seismic motion, on the nonlinear dynamic response of base-isolated reinforced concrete (r.c.)…”
Section: Introductionmentioning
confidence: 99%